2022
DOI: 10.5194/acp-22-3507-2022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in anthropogenic precursor emissions drive shifts in the ozone seasonal cycle throughout the northern midlatitude troposphere

Abstract: Abstract. Simulations by six Coupled Model Intercomparison Project Phase 6 (CMIP6) Earth system models indicate that the seasonal cycle of baseline tropospheric ozone at northern midlatitudes has been shifting since the mid-20th century. Beginning in ∼ 1940, the magnitude of the seasonal cycle increased by ∼10 ppb (measured from seasonal minimum to maximum), and the seasonal maximum shifted to later in the year by about 3 weeks. This shift maximized in the mid-1980s, followed by a reversal – the seasonal cycle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Springtime negative trends at Summit may also be due to emission reductions over North America. Our results do not suggest a shift in the O 3 seasonal cycle toward higher concentrations in the spring (i.e., moving back toward pre‐industrial O 3 seasonality) as reported at NH mid‐latitudes (Bowman et al., 2022). Another explanation for decreasing springtime O 3 at the surface could be that reductions in snow cover due to climate warming (Mudryk et al., 2020) are leading to more O 3 dry deposition to Scandinavian forests.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Springtime negative trends at Summit may also be due to emission reductions over North America. Our results do not suggest a shift in the O 3 seasonal cycle toward higher concentrations in the spring (i.e., moving back toward pre‐industrial O 3 seasonality) as reported at NH mid‐latitudes (Bowman et al., 2022). Another explanation for decreasing springtime O 3 at the surface could be that reductions in snow cover due to climate warming (Mudryk et al., 2020) are leading to more O 3 dry deposition to Scandinavian forests.…”
Section: Discussionsupporting
confidence: 55%
“…While such increases were reported previously at Utqiaġvik (A. Christiansen et al., 2022; Cooper et al., 2020) and Alert (Sharma et al., 2019), we confirm this tendency over the wider Arctic. Emission reductions of NO x in Europe and North America, and more recently over eastern Asia, have led to increasing wintertime O 3 at mid‐latitudes due to less nitrogen oxide titration of O 3 (Bowman et al., 2022; Jhun et al., 2015; T. Wang et al., 2022). This can explain observed increases in wintertime surface Arctic O 3 , influenced primarily by transport of air masses from Europe (Hirdman et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the evidence around tropospheric ozone changes has come from the analysis of surface ozone trends, especially over the United States and Europe (Yan et al, 2018a, b;Lefohn et al, 2010;Simon et al, 2015). Changes over these regions since the 1990s are often characterized by shifts in the magnitude of the seasonal cycle (Bowman et al, 2022) and decreasing peak and summertime ozone values, in contrast to the increasing annual mean ozone driven by increasing low-percentile (e.g., 5th and 10th percentile) ozone. However, changes occurring at the surface may differ from changes above the boundary layer due to the increased importance of transport processes over emissions in the FT. Trends throughout the troposphere can be investigated via satellites measuring total ozone throughout the entire atmospheric column after accounting for the stratospheric contribution.…”
Section: Introductionmentioning
confidence: 99%
“…This also suggests that anthropogenic emissions in this region have the effect of shifting the annual O 3 maximum later in the year, as has been discussed in other studies. 52,53…”
Section: Resultsmentioning
confidence: 99%
“…This also suggests that anthropogenic emissions in this region have the effect of shiing the annual O 3 maximum later in the year, as has been discussed in other studies. 52,53 NO X and SO 2 are reactive gases with a relatively short lifetime in the atmosphere. Therefore, the absolute differences in NO X and SO 2 concentrations between the simulations are largely constrained to the source regions (Fig.…”
Section: Apportionment Of Pollutants To Emissions In Quebec the Roc A...mentioning
confidence: 99%